Marxism, cultural studies and sport [ - Carrington, Ben , 1972-; McDonald, Ian , 1965- (Routledge critical studies in sport., 2009)
'Marxism, Cultural Studies and Sport' aims to contribute to the critical analysis of sport in society by joining together Marxist and Cultural Studies approaches in one volume, so as to reveal the underlying structures of power present in contemporary sporting cultures.